Characterization of the bark storage protein gene (JcBSP) family in the perennial woody plant Jatropha curcas and the function of JcBSP1 in Arabidopsis thaliana - Ming-Jun Zhang; Qiantang Fu; Mao-Sheng Chen; Huiying He; Mingyong Tang; Jun Ni; Yan-Bin Tao; Zeng-Fu Xu (PeerJ, 2022)
Background Bark storage protein (BSP) plays an important role in seasonal nitrogen cycling in perennial deciduous trees. However, there is no report on the function of BSP in the perennial woody oil plant Jatropha curcas. Methods In this study, we identified six members of JcBSP gene family in J. curcas genome. The patterns, seasonal changes, and responses to nitrogen treatment in gene expression of JcBSPs were detected by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). Overexpression of JcBSP1 in transgenic Arabidopsis thaliana was driven by a constitutive cauliflower mosaic virus (CaMV) 35S RNA promoter. Results JcBSP members were found to be expressed in various tissues, except seeds. The seasonal changes in the total protein concentration and JcBSP1 expression in the stems of J. curcas were positively correlated, as both increased in autumn and winter and decreased in spring and summer. In addition, the JcBSP1 expression in J. curcas seedlings treated with different concentrations of an NH4NO3 solution was positively correlated with the NH4NO3 concentration and application duration. Furthermore, JcBSP1 overexpression in Arabidopsis resulted in a phenotype of enlarged rosette leaves, flowers, and seeds, and significantly increased the seed weight and yield in transgenic plants.